(untitled) (Journal of Hama University, 2021)
Objectives: This study aimed to measure and compare the compressive strength of two bulk-fill composites (Beautifil Bulk Restrative and Sonicfill 2) to two conventional ones (Beautifil II and Filtek Z350XT). Materials and methods: In this in vitro study, four different types of composites were used as follows: Group 1 – Beautifil II (Shofu, Japan); group 2 – Beautifil Bulk Restrative (Shofu, Japan); group 3 – Sonicfill 2 (Kerr) and group 4 – Filtek Z350 XT (3M ESPE, St. Paul, MN, USA). 15 cylindrical samples of 5 mm height and 5 mm diameter were made in each group using a metallic mold. The composites filled in the metallic mold were photopolymerized using light-emitting diode (LED) light-curing unit and the cured samples were stored in water at 37°C for 48 hours before testing. The compressive strength of the stored samples was tested using universal testing machine (Instron) at a cross-head speed of 0.5 mm/minute. The compressive strength was calculated by dividing the maximum load with area of the samples. Results: Results were statistically analyzed using one-way analysis of variance (ANOVA). Analysis showed no statistically differences between the tested groups (P < 0.05). The highest mean value was in group 1 – Beautifil II (233.51) then group 3 – Sonicfill 2 (226.51), group 4 – Filtek Z350 XT (211.18) and finally, the lowest mean value was in group 2 – Beautifil Bulk Restorative (196.58).